Inflation, Disinflation, and Growth - Ghosh, Atish (IMF Working Papers; Working Paper, 1998)
Although few would doubt that very high inflation is bad for growth, there is much less agreement about moderate inflation's effects. Using panel regressions and a nonlinear specification, this paper finds a statistically and economically significant negative relationship between inflation and growth. This relationship holds at all but the lowest inflation rates and is robust across various samples and specifications. The method of binary recursive trees identifies inflation as one the most important statistical determinants of growth. Finally, while there are short-run growth costs of disinflation, these are only relevant for the most severe disinflations, or when the initial inflation rate is well within the single-digit range.